Anatomical and Radiographic study of the Portal and Hepatic Veins in Ovis Aris and Capras Hircus - Al- Sadi, S. (The Iraqi Journal of Veterinary Medicine, 2013)
The main purpose of this study was to convey a more precise explanation of the intrahepatic pattern of the tributaries of portal and hepatic veins in sheep and goats. Also to give broad information on the portal and hepatic vein and there topographic relation that may give a useful base for the hepatic segmentation, aiming to provide a correct base for surgical procedures and liver transplantation. Twelve livers collected from adult sheep and goats of both sexes. The portal and hepatic veins were studied by using cross dissection, corrosion cast and radiographic examination.Subject of this investigation show the portal vein of the sheep is slightly narrower than that of the goat. Also the pattern of intrahepatic branches of portal vein in sheep is similar to that of goat. on reaching the portal hepatic, gave of a right dorsal interlobular branch and then terminate into a right ventral interlobular and left interlobular branches , the right dorsal interlobular branch was short and large, supplied the caudate process and right dorsal hepatic lobe .The right ventral interlobular branch is distributed only in the ventral part of the right lobe, while the left branch was long and narrow, supplied the left and quadrate lobes as well as the papillary process, However the caudate process receives the separate branch from the parotid vein in goat. Moreover, the study revealed that the hepatic veins in sheep and goats can be classified into two groups ; large and small , the work also shows that there are (3-4) large hepatic veins in sheep, while in goats usually gives off a left large branch and two smaller right and intermediate branches, and in both animals the hepatic vein, pour in the caudal vena cava independently, the veins of the left, right and intermediate lobes empty themselves close to each other, while of these of the caudate and papillary processes open separately and a way from hepatic veins